(untitled) (Research, Society and Development, 2020)
In this article, we highlighted characteristics of the training and teaching work processes, in the context of the Institutional Program for Teaching Initiation Scholarships (Pibid), which matters in the qualification process of teacher training and which occurs within the scope of Mathematics Degree courses, from qualitative research supported by textual discursive analysis of productions, 26 theses and dissertations. The characteristics of Pibid does not only contributes to the student’s permanence in the Degree course, but also proposes an investigative scenario and can provide an increase in interest in the teaching area, as well as transformations in practices, questioning his own knowledge and the knowledge of the practice of others. This is not an investigation aimed only at discoveries, but also towards a critical attitude towards the context in which it is inserted. The initiation scholarship holder is therefore allowed to problematize the context and consider the knowledge produced at the academy and the knowledge produced at school in the foreground. Pibid is an educational policy, which has the potential to improve teaching and learning, leads to an investigative process and consequently becomes an education for democracy.